2017
DOI: 10.1177/1729881416686955
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional variable stiffness hydraulic actuator for load-carrying knee exoskeleton

Abstract: This article presents the design and experimental testing of a unidirectional variable stiffness hydraulic actuator for loadcarrying knee exoskeleton. The proposed actuator is designed for mimicking the high-efficiency passive behavior of biological knee and providing actively assistance in locomotion. The adjustable passive compliance of exoskeletal knee is achieved through a variable ratio lever mechanism with linear elastic element. A compact customized electrohydraulic system is also designed to accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The swing phase consists of two subphases: initial (toe off to knee maximum flexion) and terminal swing (knee maximum flexion to heel strike) [16,17]. The main function of the knee in the swing phase is assisting flexion-extension for toe clearance, foot placement, and taking over the load in the next step [19,20]. Zheng [21] reported that the knee biomechanics is affected mainly by walking speed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The swing phase consists of two subphases: initial (toe off to knee maximum flexion) and terminal swing (knee maximum flexion to heel strike) [16,17]. The main function of the knee in the swing phase is assisting flexion-extension for toe clearance, foot placement, and taking over the load in the next step [19,20]. Zheng [21] reported that the knee biomechanics is affected mainly by walking speed.…”
mentioning
confidence: 99%
“…During walking, running, and stair climbing, a high stiffness in the weight acceptance phase and a low stiffness in the swing phase can be observed. For walking, Zhu et al [20] and Wang [12] found that the knee quasistiffness was around 3.0 and 2.27 Nm/deg in the stand phase. Sridar et al [34] indicated E: first peak knee extension moment; F: first peak knee flexion moment; G: second peak knee extension moment; H: second peak knee flexion moment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, for the wearer to bend the knee, a controller opens solenoid valves and the wearer has to bend the knee joint of the robot. This makes the wearer feel tired and has the disadvantage of the slow response [12][13][14]. Such conventional hydraulic systems are complicated because of solenoid valves and have problems such as leakages.…”
Section: Introductionmentioning
confidence: 99%
“…Borisoff et al proposed a concept that combines the characteristics of the wheelchair with an exoskeleton using the wheelchair for the movement and the exoskeleton for the rehabilitation. 17 The exoskeleton design has become a research hot spot with solutions that now provide specific advantages in strength enhancement 18,19 and rehabilitation tasks [20][21][22][23] for humans. For example, the Honda exoskeleton was designed to support the wearer's body weight, which reduces strain on the articulations in the knees, ankles, and hips.…”
Section: Introductionmentioning
confidence: 99%